Has fire suppression increased the amount of carbon stored in western U.S. forests? - Aaron W. Fellows; Michael L. Goulden (Geophysical Research Letters)
Active 20th century fire suppression in western US forests, and a resulting increase in stem density, is thought to account for a significant fraction of the North American carbon sink. We compared California forest inventories from the 1930s with inventories from the 1990s to quantify changes in aboveground biomass. Stem density in mid‐montane conifer forests increased by 34%, while live aboveground carbon stocks decreased by 26%. Increased stem density reflected an increase in the number of small trees and a net loss of large trees. Large trees contain a disproportionate amount of carbon, and the loss of large trees accounts for the decline in biomass between surveys. 20th century fire suppression and increasing stand density may have decreased, rather than increased, the amount of aboveground carbon in western US forests.